Martyrs and players in early modern England : tragedy, religion and violence on stage - Anderson, David K., 1978- (Studies in performance and early modern drama., 2014)
Focusing on Christopher Marlowe, William Shakespeare, John Webster and John Milton, Martyrs and Players in Early Modern England argues that the English tragedians reflected an unease within the culture to acts of religious violence. David Anderson explores a link between the unstable emotional response of society to religious executions in the Tudor-Stuart period, and the revival of tragic drama as a major cultural form for the first time since classical antiquity.